The Role of Community Cooperative Institutions in Building Rural–Urban Linkages Under Urbanization of Pastoral Regions in China - Gongbuzeren,; Wenjun, Li; Yupei, Lai (Frontiers in Sustainable Food Systems, 2021)
In contrast to agricultural settings, the process of urbanization in the pastoral regions of China are largely driven by long-term influences of ecological conservation and the provision of social services. Consequently, many of the herders who have migrated into nearby secondary urban centers depend on resources from pastoral regions to support their livelihoods, forming complex patterns of rural–urban linkages. While current literature has discussed the processes of herder out-migration and their implications on rural and urban livelihood development, few studies have examined the linkages between the herders living in the pastoral regions and those who have out-migrated to urban regions and their importance in rural livelihood transformation. Based on past studies, we argue that, in a changing pastoral social–ecological system, herders living in both rural and urban regions depend on each other to support their livelihoods through three types of mobility: (1) livestock mobility, (2) herder mobility, and (3) resource mobility. However, what innovative institutions in rangeland resource management and herder economic cooperation can do to help maintain these three types of mobility to sustain rural livelihood development, becomes a critical challenge. Innovative community cooperative institutions developed by pastoral communities from the Tibetan Plateau and Inner Mongolia may be able to offer new perspective and insight on how to better maintain rural–urban linkages in the processes of urbanization in pastoral regions. In this current study will present the two cases of innovative institutions and the roles they play in facilitating the three types of mobility to address livelihood challenges. While current studies recommend an increase of government subsidies, provision of vocational training, and social insurance that help herders better adapt to urban livelihood, we argue that rangeland management and community economic cooperation in innovative institutions are needed to facilitate the mobility of livestock, resources, and the herder population, and maybe only then the livelihood challenges that migrated herders are facing will be addressed effectively.